A 61 Year Old Woman With Hypoglycemia on Diabetes Mellitus due to Sulphonylurea , Urinary Tract Infection, Hypertension, Cholelithiasis, Kidney Disorder: A Case Report - Rahmat Yusuf Arifin; Rachmad Aji Saksana; Indra Setya Permana; Anggi Fitria Kusumaningtyas (The International Journal of Medical Science and Health Research, 2025)
Background : Hypoglycemia is defined as a condition of plasma glucose below normal limits. The most common cause of hypoglycemia is the use of antidiabetic drugs from sulphonylurea and can be exacerbated by renal function disorder. We report hypoglycaemia caused by sulfonylurea and kidney disorders as well as treatment selection in patients with Diabetes Mellitus (DM) with kidney disorder in Chronic Kidney Disease (CKD) patients especially with Glomerular Filtration Rate (GFR) < 30 ml/min/1.73 m 3 . Case Report : The 61-year-old woman, came with a complaint of loss of consciousness for two hours before entering the hospital, previously the patient complained of dizziness. Patients have a history of diabetes mellitus and hypertension. Patients regularly take metformin, glimepirid and captopril. Vital signs blood pressure 170/85 mmHg, heart rate 86x/min, respiratory rate 22x/min, temperature 36.3 oC , oxygen saturation 99%, lateralization not found. The blood glucose test showed 28 mg/dL. Laboratory results of kidney function showed urea 134mg/dL and creatinine 8.8mg/dL. Treatment using a hypoglycemia algorithm, with Dextrose 40% and Dexamethasone, provides a good effect so that hypoglycemia does not occur again. Discussion : The choice of antidiabetic drugs in DM patients with high risk factors for hypoglycemia and kidney disorder needs to be considered. Hypoglycaemia is caused by the failure of counter-regulation processes in the body triggered by insulin. Insulin production increases due to the effects of sulphonylurea drugs. CKD exacerbates the condition of hypoglycemia by decreasing the process of insulin degradation and gluconeogenesis. Conclusion : This case underscores the necessity of vigilant drug selection, renal-adjusted dosing, and comprehensive care to mitigate hypoglycemia risk in DM patients with CKD, ultimately improving clinical outcomes and quality of life. Prevention of hypoglycaemia and selection of DM therapy in patients with kidney disorders requires special attention by paying attention to the side effects of the drug and the success of therapy. Drug therapy options that can be given are metformin, SGLT-2 in the drug canaglifozin , thiazolidinediones, new generation sulfonylureas, DPP-4 inhibitors, and insulin with dose adjustments. Hypoglycemia can be prevented by maintaining the patient's symptoms and self-monitoring blood glucose.